Why it wasn't a great victory after all - Wietse Buijs (Amsterdam Law Forum, 2012)
On the last day of 2011, President Obama signed a law affirming his power to detain suspected terrorists indefinitely. It is a next strike in an on-going turf war between the Obama Administration and the Supreme Court. A turf war that should have been over in 2008 when a landmark case Boumediene v. Bush granted the right to challenge their confinement to the detainees. Except the war wasn't over at all. The Federal Court appointed as the Appellate Court in detainee cases is not keen on implementing the Boumediene precedent at all. An answer from the Supreme Court is expected, but is not given. Why not?